Assessment of daily behaviors associated with myopia among undergraduate’s students in UiTM Puncak Alam Campus / Muhammad Farid Ismail - Ismail, Muhammad Farid (2011)
This research, which is on myopia, was done among undergraduates’ students in Universiti Teknologi Mara (UiTM) Puncak Alam Campus. The primary objective of this study was to identify the prevalence by gender, awareness and most common factors associated with myopia among undergraduates’ students in UiTM Puncak Alam. This research was based on a cross sectional design template. We took all the students as our sample but assessed those who need prescription eyewear on their daily activities. The result showed that 57.8% (N=231) of undergraduates’ students are myopic. In term of gender, about 24.7% (N=57) of male students are myopic. For the female, about 75.3% (N=174) of them are having myopia. In conclusion, undergraduates’ students in UiTM Puncak Alam may have higher prevalence of myopia.